Married in name only - Bennett, Jules (Texas Cattleman's Club: Houston., 2019)
Paisley Morgan just discovered that Texas<U+2019>s most infamous billionaire could be her real father. Now she needs the help of her infuriating and incredibly sexy ex, investigator Lucas Ford. But Lucas will accept only one payment: Paisley<U+2019>s hand in marriage. But will his thirst for revenge outlast their passion-filled nights as Paisley proves to be much more than a wife in name only?